2007
DOI: 10.1037/0021-843x.116.2.378
|View full text |Cite
|
Sign up to set email alerts
|

Nonnormality and divergence in posttreatment alcohol use: Reexamining the Project MATCH data "another way."

Abstract: Alcohol lapses are the modal outcome following treatment for alcohol use disorders, yet many alcohol researchers have encountered limited success in the prediction and prevention of relapse. One hypothesis is that lapses are unpredictable, but another possibility is the complexity of the relapse process is not captured by traditional statistical methods. Data from Project Matching Alcohol Treatments to Client Heterogeneity (Project MATCH), a multisite alcohol treatment study, were reanalyzed with 2 statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
79
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 80 publications
(138 reference statements)
3
79
0
1
Order By: Relevance
“…It refers to a sudden change or "jump" that will occur at different values of the asymmetry variable, depending on the direction of the change in this variable (Witkiewitz et al, 2007). The concept of hysteresis is illustrated in Figure 2: within a defined range of the underlying challenge parameter (X 1 -X 2 ), the employee can be observed functioning on either two branches -a lower branch associated with the process of differentiation (Csikszentmihalyi, 1993), this is, recognizing some opportunity for action or challenge, or an upper branch associated with the integration process (Csikszentmihalyi, 1993), acquisition and assimilation of skills involved in the activity.…”
Section: Hysteresismentioning
confidence: 99%
“…It refers to a sudden change or "jump" that will occur at different values of the asymmetry variable, depending on the direction of the change in this variable (Witkiewitz et al, 2007). The concept of hysteresis is illustrated in Figure 2: within a defined range of the underlying challenge parameter (X 1 -X 2 ), the employee can be observed functioning on either two branches -a lower branch associated with the process of differentiation (Csikszentmihalyi, 1993), this is, recognizing some opportunity for action or challenge, or an upper branch associated with the integration process (Csikszentmihalyi, 1993), acquisition and assimilation of skills involved in the activity.…”
Section: Hysteresismentioning
confidence: 99%
“…Other researchers have shown that object perception and event prediction also shows hysteresis [van Rooij et al, 2002]. Researchers examining interindividual differences have applied catastrophe models to the study of political attitudes [van der Maas et al, 2003] and have found that small differences in selfefficacy predict large differences between individuals in abstinence from alcohol [Witkiewitz, van der Maas, Hufford, & Marlatt, 2007].…”
Section: Catastrophe Modelsmentioning
confidence: 99%
“…(p. 1,328). Second, the analyses conducted in Project MATCH have been called into question because the researchers relied on the general linear model and ignored the heterogeneity of posttreatment alcohol use (Witkiewitz et al, 2007). In response to several criticisms, the Project MATCH Research Group recognized that, "Perhaps if we had examined the data in another way, the results might have been different" (Project MATCH Research Group, 1999, p. 69).…”
mentioning
confidence: 99%
“…The categorical latent variable defines the multiple latent "classes" (often thought of as subpopulations), each with its own estimates of growth factors that represent the mean intercept and slope for all the individuals grouped into that class. Recently a number of GMMs have been applied to characterize heterogeneity in longitudinal drinking outcomes and identify covariates (Chassin et al, 2002;Greenbaum et al, 2005;Jackson and Sher, 2005;Witkiewitz et al, 2007).…”
mentioning
confidence: 99%